Paper based electronic tongue – a low-cost solution for the distinction of sugar type and apple juice brand. Issue 8 (19th March 2019) - Daikuzono, Cristiane M.; Delaney, Colm; Morrin, Aoife; Diamond, Dermot; Florea, Larisa; Oliveira, Osvaldo N.
Abstract : This work reports on a low cost microfluidic electronic tongue (e-tongue) made with carbon interdigitated electrodes, printed on paper, and coated with boronic acid-containing hydrogels. Abstract : This work reports on a low cost microfluidic electronic tongue (e-tongue) made with carbon interdigitated electrodes, printed on paper, and coated with boronic acid-containing hydrogels. Using capacitance measurements, the e-tongue was capable of distinguishing between different types of sugars ( e.g. glucose, fructose and sucrose), in addition to distinguishing between commercial brands of apple juice using a small volume of sample (6 μL). The channels of the microfluidic e-tongue were made using a wax printer, and were modified with hydrogels containing acrylamide copolymerized with 5 or 20 mol% 3-(acrylamido) phenyl boronic acid (Am-PBA), or a crosslinked homopolymeric hydrogel based on N -(2-boronobenzyl)-2-hydroxy- N, N -dimethylethan-1-aminium-3-sulfopropyl acrylate (DMA-PBA). Such hydrogels, containing a phenyl boronic acid (PBA) moiety, can bind saccharides. Combining various hydrogels of this nature in an e-tongue device enabled discrimination between apple juices, which are known to contain higher amounts of fructose compared to glucose or sucrose. Changes in capacitance were captured with impedance spectroscopy in the frequency range from 0.1 to 10 MHz for solutions with varying concentrations of glucose, fructose and sucrose (from 0 to 0.056 g mL −1 ). The capacitance data were treated with Principal Component Analysis (PCA) and Interactive Document Map (IDMAP), which then correlated overall sugar content from different brands of apple juice. This low-cost, easy-to-use, disposable e-tongue offers great potential in the routine analysis of food and beverages, while offering comparative performance to alternatives in the literature.